Food web dynamics in a seasonally varying wetland - Donald L. DeAngelis; Joel C. Trexler; Douglas D. Donalson (Mathematical Biosciences and Engineering)
A spatially explicit model is developed to simulate the small fish communityand its underlying food web, in the freshwater marshes of the Everglades.The community is simplified to a few small fish species feeding onperiphyton and invertebrates. Other compartments are detritus, crayfish, anda piscivorous fish species. This unit food web model is applied to each ofthe 10,000 spatial cells on a 100 x 100 pixel landscape. Seasonal variationin water level is assumed and rules are assigned for fish movement inresponse to rising and falling water levels, which can cause many spatialcells to alternate between flooded and dry conditions. It is shown thattemporal variations of water level on a spatially heterogeneous landscapecan maintain at least three competing fish species. In addition, theseenvironmental factors can strongly affect the temporal variation of the foodweb caused by top-down control from the piscivorous fish.